On the identity of species of the huntsman spider genus Thelcticopis Karsch, 1884 (Araneae: Sparassidae: Sparianthinae) from India, Myanmar, Pakistan, and Sri Lanka - Sankaran, Pradeep M.; Sherwood, Danniella; Jäger, Peter (Zootaxa, 2024)
The species of the genus Thelcticopis Karsch, 1884 from India, Myanmar, Pakistan, and Sri Lanka are reviewed. Stasina nalandica Karsch, 1892 and S. paripes (Karsch, 1879) are re-transferred to the genus Thelcticopis. Thelcticopis ajax Pocock, 1901, T. bicornuta Pocock, 1901, T. birmanica Thorell, 1895 stat. rev., T. hercules Pocock, 1901, T. moolampilliensis Sunil Jose & Sebastian, 2007, T. nalandica (Karsch, 1892) comb. rest., T. paripes (Karsch, 1879) comb. rest., T. picta (Thorell, 1887), T. rufula Pocock, 1901, T. serambiformis Strand, 1907, and T. virescens Pocock, 1901 are diagnosed, redescribed, and/or illustrated based on type and/or freshly collected material, and their current distributional records are mapped. The female of T. virescens is described for the first time. The type locality of Thelcticopis goramensis (Thorell, 1881) is situated in Indonesia, Maluku, not in Malaysia. Thelcticopis bifasciata (Thorell, 1891), and T. fasciata (Thorell, 1897) are proposed as nomina dubia as the holotypes are immature and their identity cannot be fully elucidated. Thelcticopis ancorum Dyal, 1935 and T. telonotata Dyal, 1935 from Lahore, Punjab are considered species incertae sedis, and the subfamily Sparianthinae is most likely not distributed in Pakistan.